2014
DOI: 10.1002/elsc.201200184
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity, the chemical composition of biomass and photosynthetic activity ofChlorella vulgarisunder different light spectra in photobioreactors

Abstract: Omitting the far‐red in LED lighting for bioreactors is inexplicable because it affects photosynthetic efficiency and photomorphogenetic activity. Therefore, this work compares three light sources (fluorescent—white light (WL), and LED: blue + red—BRL and blue + red + far‐red—BRFRL) for cultures of Chlorella vulgaris. Metabolic activity was determined by isothermal calorimetry. Changes in the chemical composition of biomass were examined by spectrofluorimetry and Raman spectroscopy. Maximum quantum yield of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 43 publications
5
28
1
1
Order By: Relevance
“…, in terrestrial plants, several cinnamic acids (ferulic, sinapsis, and caffeic acid) are responsible for the so‐called F450, whereas the F530 is attributed to compounds such as berberine, quercetin, and riboflavin. Similar shifts in the fluorescence spectra, suggesting changes in the composition of phenolic compounds, were observed previously during the growth of Chlorella vulgaris culture .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…, in terrestrial plants, several cinnamic acids (ferulic, sinapsis, and caffeic acid) are responsible for the so‐called F450, whereas the F530 is attributed to compounds such as berberine, quercetin, and riboflavin. Similar shifts in the fluorescence spectra, suggesting changes in the composition of phenolic compounds, were observed previously during the growth of Chlorella vulgaris culture .…”
Section: Resultssupporting
confidence: 85%
“…According to Lang et al [41], in terrestrial plants, several cinnamic acids (ferulic, sinapsis, and caffeic acid) are responsible for the so-called F450, whereas the F530 is attributed to compounds such as berberine, quercetin, and riboflavin. Similar shifts in the fluorescence spectra, suggesting changes in the composition of phenolic compounds, were observed previously during the growth of Chlorella vulgaris culture [34,42]. Fluorescence emission spectra can produce many relevant information regarding plant responses to changing growth conditions, for example, the intensity and/or spectrum of light, temperature, and nutrient deficiency.…”
Section: Phenol Content and Blue-green Fluorescence Emission Spectrasupporting
confidence: 70%
“…The results obtained in the present study were not compared to those obtained for WL, because it was demonstrated earlier that WL is definitely the best source of light for C. vulgaris cultures in photobioreactors [10].…”
mentioning
confidence: 88%
“…In previous work we have demonstrated that the addition of FR to LED matrix emitting blue-R light (BR) light had a positive effect on the metabolism of microalgae [10]. Due to the fact that in that study the BRFRL (blue + R + FR light) source-composed of two FR LEDs 720 and 740 nm (with a peak at about 730 nm)-was used, we decided to investigate whether it was necessary to apply "such a complicated source of BRFRL."…”
mentioning
confidence: 99%
“…Furthermore, the accumulation of other internal components of microalgae would be also affected by pesticides. Some algae have been widely used in environmental study, such as Chara coralline, Microcystis aeruginosa, Scenedesmus and Chlorella species (Li et al 2008;McGinn et al 2012;Kula et al 2014;Liu et al 2014;Abinandan et al 2015). As recognition element, microalgae also become an extremely important part of the biosensor in detecting pesticides (Orellana et al 2007;Ebenezer et al 2012;Perullini et al 2014).…”
Section: Introductionmentioning
confidence: 99%